Why do English speakers incorrectly construct the sentence Por las tardes yo practicar deportes? : A SDG to promote interlinguistic reflection on the subject and the verb in English and Spanish - Abad Beltrán, Victoria (Huarte de San Juan. Filología y Didáctica de la Lengua, 2023)
This paper presents the results of a classroom investigation whose data is extracted from the implementation in a group of 3rd ESO of a didactic grammar sequence (SDG) designed according to the model proposed by the Egramint project. Thus, it starts from the analysis and observation of linguistic uses from a multilingual perspective to promote interlinguistic reflection on the relationships between the subject and the verb in Spanish and English from the question: Why do English speakers incorrectly construct the sentence Por las tardes yo practicar deportes? Oral interaction during the implementation of the sequence and students written reflections on their learning process show that the integrated treatment of languages ​​enhances their metalinguistic awareness and that, when faced difficulties in constructing grammatical knowledge, they preferentially resort to context or meaning.
Keywords: grammar teaching; interlinguistic reflection; didactic sequence; verb agreement; pedagogical grammar